Indications and possible limitations using medio-plantar plate systems in tarsometatarsal 1 fusions – A cadaveric study - Winter, Philipp; Klos, Kajetan; Lambert, Laura; Paulsen, Friedrich; Landgraeber, Stefan; Wagener, Joe (Annals of Anatomy-Anatomischer Anzeiger, 2023)
Background: The tarsometatarsal 1 arthrodesis is an adequate treatment for moderate to severe hallux valgus deformity and instability of the first ray. Plantar plating arthrodesis has been shown to provide better mechanical stability and fewer postoperative complications than screw fixation or medial plating. The medio-plantar plate is a new plate design for Lapidus arthrodesis. It could combine the biomechanical advantages of the plantar plate and the anatomical overview of a medial plate. However, the implanted material can cause irritation of the tibialis anterior, which in some cases may require removal of the material. The purpose of this study was to examine the possibility of tendon irritation following medio-plantar first tarsometatarsal joint arthrodesis using cadaveric specimens. Methods: The study involved the simulated surgical procedure of medio-plantar plate arthrodesis on 30 lower extremities. After the plates were fixed, a thorough examination of the feet was conducted to assess any tendon irritation and to determine a recommendation for placement of the medio-plantar plate based on the Olewnik classification. Results: Irritation of the tibialis anterior tendon components with the medio-plantar plate depends mainly on the anatomic norm variant, classified according to Olewnik et al. A medio-plantar plate is particularly recommended in TA tendon Olewnik type 3 and type 5. The positioning of a medio-plantar plate in Olewnik type 1 and type 2 tendons depends on the anatomic fit of the medio-plantar plate and the bony configuration of the TMT 1 joint. A large portion of the TA tendon must be detached, so a different plate design may be preferred in these patients. Conclusions: TMT 1 arthrodesis with medio-plantar plating of the first tarsometatarsal joint should be performed considering the anatomic TA tendon variations. Level of evidence: Level V, Expert Opinion includes Case Reports and Technique Tips.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Hallux valgus; Lapidus; Medio-plantar plate; Plantar plate; Tarsometatarsal arthrodesis; Tendon irritation; Tibialis anterior